REAKTUALISASI PANCA DHARMA TAMAN SISWA DALAM PENDIDIKAN ABAD KE-21 - Dewa Made Dwicky Putra Nugraha (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The dynamics of global education brings the Indonesian nation to reflect on the basic values of the current national education administration. Ki Hajar Dewantara's teachings on the concept of the Panca Dharma Taman Siswa, became a flashback to Indonesian education that needs to be re-actualized in the 21st century education. This paper aimed at elaborating the essence of the reactualization of Panca Dharma Taman Siswa which consists of nature, independence, culture, nationality principles and humanity in 21st century education. The teachings of the five dharmas are considered to be the principles of education that are very relevant in responding to the symptoms of globalization in the 21st century. (1) The principle of nature, returning the principle of learning to natural interactions with the environment, therefore humans can develop naturally; (2) The principle of independence provides the widest possible space for students to achieve their best abilities; (3) the principle of culture, creating the process of inheriting the nation's culture and internalizing values that are manifested in the daily lives of students; (4) The principle of nationality, education forms a nationalist person with a mindset that is open to the world; and (5) the principle of humanity, education shapes students to become real human beings through a humanist approach.